(untitled) (Journal of Information Technologies in Education (ITE), 2012)
The article presents the main characteristics of software as a service on the Internet for education leading companies Google, Microsoft, IBM. There are described some actions of these companies, which are conducted to help teachers to master cloud technology for improve the professional activities.